Perceptions of stigma among people with lived experience of methamphetamine use within the hospital setting: qualitative point-in-time interviews and thematic analyses of experiences - Forchuk, Cheryl; Serrato, Jonathan; Scott, Leanne (Frontiers in Public Health, 2024)
Objectives: As part of a larger mixed-methods study into harm reduction in the hospital setting and people with lived experience of methamphetamine use, stigma was a prominent issue. The aim of this secondary analysis was to investigate the issue of stigma. Design: Participants completed a one-time qualitative interview component to assess their experiences in the hospital setting. Setting: Secondary and tertiary care in Southwestern Ontario, Canada. Participants who had received care from these settings were also recruited from an overdose prevention site, a primary health care centre, a national mental health organisation, an affordable housing agency, and six homeless-serving agencies between October 2020 to April 2021. Participants: A total of 104 individuals completed the qualitative component of a mixed-method interview. Sixty-seven participants identified as male, 36 identified as female and one identified as non-binary. Inclusion criteria included past or current use of methamphetamine, had received services from a hospital and able to communicate in English. Methods: Open-ended questions regarding experiences in the hospital setting were asked in relation to lived experience of methamphetamine. A secondary analysis was conducted post-hoc using a thematic ethnographic approach due to prominent perceptions of stigma. Results: Three themes were identified. The first theme identified substance use was perceived as a moral and personal choice; the second theme pertained to social stigma such as income, housing, and substance use and consequences such as being shunned or feeling less worthy than the general patient population; the third theme highlighted the health consequences such as inadequate treatment or pain management. Conclusions: This study revealed that stigma can have consequences that extend beyond the therapeutic relationship and into the healthcare of the individual. Additional training and education for health care providers represents a key intervention to ensure care is nonstigmatizing and patient-centered as well as changing hospital culture.